The Importance of Special Coordination Skills in Goal Shoting by U-12 Soccer Players - Elva Katherine Aguilar Morocho, Karla Natalia Rivadeneira Arias, Maritza Gisella Paula Chica, Kelly Deysi Hernández Mite (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Soccer is a worldwide sport, and its practice at early ages is an essential aspect. One of its fundamentals is goal shooting, which is a technical activity that involves kicking the ball into the opponent's goal. This can be done with the lower limbs, trunk, and head. This action is directly related to coordinative abilities, which are an important element in formative soccer training, and a vital part of this research. It was established as an objective to substantiate the significance of special coordination skills training in goal shooting by U-12 soccer players. The methodology was based on a theoretical review, which uses methods such as the analytical-synthetic for the processing and analysis of information, as well as the inductive-deductive method to go from the more specific (as in the goal shooting) to the more general (as in the sportsman's coordination development in the goal shooting technique). The type of research is documentary, through which an analysis of the secondary data information is established. Among the primary findings, there were some researchers who determined that coordination exercises enhance children's technique at early ages. Therefore, they improve areas such as control, stability, and goal shooting.